A comunicação na perspectiva homem-máquina: um estudo sobre interações de uma equipe em torno de um software a partir das percepções de gestores - Carvalho, Guilherme Moreira de (2018)
This dissertation aimed to discuss the communication interactions in the "man-machine" perspective suggested by Morgan (1998) based on the perception of managers of a departmental unit (entitled "Mother Board"). To reach the objectives, the qualitative and exploratory methodology was adopted. Interviews were conducted (semi-structured questions), with the purpose of verifying the perception about the communication flows established in the system entitled "Management Information System Z - Portfolio of Programs and Projects", with reference to the cognitive operators of Complexity commented on by Mariotti (2007), such as "1- Subject-Object Interaction"; 2 - "Circularity"; 3- "Dialog Operator"; 4- "Self-production" and 5- "Hologram Operator". Finally, the research results pointed to the perception of pragmatic and functional communication as the guiding principle of the work team of the "Mother" Board. The metaphor "man-machine" represents a dimension of work and the team, relating to other knowledge and contexts such as culture, chance and imponderable (Complexity).